Efectos del marcaje al hombre sobre la frecuencia cardíaca, el esfuerzo percibido y la demanda técnico-táctica en jóvenes jugadores de fútbol - Sanchez-Sanchez, J.; Carretero, M.; Assante, G.; Casamichana, D.; Los Arcos, A. (Revista Internacional de Ciencias del Deporte, 2016)
The aim of this research was to analyse the heart rate (HR), the perceived exertion (PE), and the technical-tactical demand in several small-sided games (SSGs) with standard goals and different defence schemes (no man-marking vs man-marking). Twelve football players whose age was 17.5±0.8 years old performed 4 different kinds of SSGs (3 sets of 4 min): 3 vs. 3 and 6 vs. 6 with and without man-marking. The load of SSGs was quantified by HR and PE. In addition, each SSGs was video recorded with the aim to analyse technical-tactical performances. The PE was higher in man-marking (p<0.05) compared to no man-marking in both 3 vs. 3 and 6 vs. 6 SSGs (7.0 ±1.2 vs. 5.2 ±1.2 y 5.4 ±1.1 vs. 4.0 ±0.7, (7.0 ±1.2 vs. 5.2 ±1.2 and 5.4 ±1.1 vs. 4.0 ±0.7, respectively). However, no differences were shown (p>0.05) by HRmax for the very same SSGs (87.7 ±3.7 vs. 87.1 ±3.5%, 3 vs. 3; 85.0 ±4.0 vs. 83.1 ±5.0%, 6 vs. 6). Successful ball-passing, the number of interventions and the control-passing actions were significantly higher (p<0.05) in the 6 vs. 6 no man-marking vs. man-marking. The results suggest that interchangeability between the HR and PE must be applied cautiously when assessing SSGs intensity/load. The defence used in SSGs influences the technical-tactical demands.